Are the Gottschee Germans in diaspora a part of Slovene emigration? - Moric, Anja (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2021)
Slovene nationalism has developed along the lines of the so-called Eastern nationalisms, which are characterised by their understanding of culture and ethnicity as the fundamental unifying element of a nation. Accordingly, the prevailing view is that the Slovene nation and Slovene emigration are based on Slovene ethnic origin and the Slovene language, wherefore the members of other ethnic groups (Germans, Hungarians, Jews, etc.) are excluded from the concept of Slovene nationhood or Slovene emigration, despite their longstanding presence in the territory of the Republic of Slovenia. Indeed, the question arises; if they do not belong to Slovene emigration, to whose emigration do they belong? Based on the civic (voluntaristic, territorial) understanding of the nation and field research conducted among the Gottscheer diaspora in the USA, Canada, Austria and Germany, I analyse the problem described in the case of Gottschee Germans.
Keywords: diaspora; Gottschee Germans; Gottscheers; identiteta; identity; kočevski Nemci; manjšine; minorities; nacionalizem; nationalism; Slovene emigration; Slovene Germans; slovenski Nemci; slovensko izseljenstvo